LITERATURE REVIEW : Hubungan Durasi Lama Duduk Terhadap Walking Speed Pada Lansia - Fimelia Putri Anindya (2020)
Background: old age can change the posture and functional of a person. The effect of prolonged sitting activity may result in a decrease in physical performance which in this study focused on walking speed. Objectives: In this study aims to find a causal relationship that is by sitting time or sedentary behavior against walking speed in the elderly. Method: The method used in this research is literature review. The literature searches through articles published through Internet sites, such as Google Scholar, PUBMED, EBSCO, Garuda Portal, and various other journal sites. Articles or journals that meet the inconclusion and exclusion criteria that have been analyzed. Literature Riview which is used by the publication of the last 5 years 2015-2020. Researched journal criteria is a journal or article based on Indonesia or English with elderly human Subjects, the journal is still related to the problem in research with the theme of elderly health and the level of walking speed in the elderly. Results: Four of the five journals that have been found indicate the long duration of relationship sitting with walking speed.